Atividade hipolipidêmica do disseleneto de difenila na hiperlipidemia induzida por Triton WR-1339 em camundongos - Rocha, Juliana Trevisan da (2009)
In mammals, the liver plays a central role in whole-body lipid metabolism. Unfortunately, dysregulation of these pathways has been implicated in hyperlipidemias. In recent years, a significant association between the trace element selenium and hypercholesterolaemia in human and animals has been reported. This study was designed to investigate a potential hypolipidaemic effect of diphenyl diselenide ((PhSe)2) in Triton WR-1339-induced hyperlipidaemia in mice. Triton was administered intraperitoneally (400 mg/kg) to overnight-fasted mice to develop acute hyperlipidaemia. (PhSe)2 was administered orally (10 mg/kg) 30 min before Triton. At 24 h after Triton injection, blood samples were collected to measure plasma lipid levels. The hepatic thiobarbituric acid reactive substances and ascorbic acid levels as well as catalase and glutathione peroxidase activity were recorded. (PhSe)2 administration significantly lowered total cholesterol, non-high- density lipoprotein-cholesterol and triglycerides,whilst it increased high-density lipoprotein-cholesterol levels in plasma of hyperlipidaemic mice. Neither oxidative stress nor the antioxidant effect of (PhSe)2 was observed in the mouse liver in this experimental protocol. These findings indicated that (PhSe)2 was able to lower plasma lipid concentrations. Further studies are needed to elucidate the exact mechanism by which (PhSe)2 exerted its hypolipidaemic effect in the management of hyperlipidaemia.